2020
DOI: 10.1017/jfm.2020.480
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of two-layer channel flow with soluble surfactant below or above the critical micelle concentration

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Recently the present authors showed that for the inertialess channel flow problem, the ability of the surfactant to dissolve in one of the fluids can either enhance or suppress interfacial instability for certain fluids and/or surfactant properties [9,10]. Studies of the related problem of film flow down an inclined substrate have found surfactant solubility to have a destabilising effect [11][12][13].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently the present authors showed that for the inertialess channel flow problem, the ability of the surfactant to dissolve in one of the fluids can either enhance or suppress interfacial instability for certain fluids and/or surfactant properties [9,10]. Studies of the related problem of film flow down an inclined substrate have found surfactant solubility to have a destabilising effect [11][12][13].…”
Section: Introductionmentioning
confidence: 86%
“…where H = 1 + h 2 x and the notation [F i ] 1 2 = F 1 − F 2 is used. The surface tension in conditions (3) is given by the Langmuir equation of state which is γ = 1 + Ma ln (1 − Γ ) [16,18] and is seen to depend on the interfacial surfactant concentration Γ , the evolution of which is described by the convection-diffusion equation [10,19] 1…”
Section: Linear Stability Analysismentioning
confidence: 99%
“…Consequently, exploiting the disparity between the and length scales, we perform a lubrication analysis to derive the following model system that will allow us to study the nonlinear spatio-temporal interfacial dynamics (see Appendix A for a detailed derivation): where , , , are all functions of and are defined by The functions and are positive provided that , while the functions and can each be of either sign depending on the values of , and . The lubrication model presented above is similar to the model of Tilley, Davis & Bankoff (1994) and it reduces to those obtained in related studies on channel flows with surfactant (Blyth & Pozrikidis 2004; Frenkel & Halpern 2017; Kalogirou & Blyth 2020), in the case when surfactant is neglected.…”
Section: Mathematical Modelmentioning
confidence: 88%
“…We note that the flow rate can be found by satisfying a periodicity condition on the pressure (Ooms et al. 1985; Blyth & Pozrikidis 2004; Kalogirou & Blyth 2020), e.g. or equivalently fixing the pressure drop in the streamwise direction to be zero over a specified domain of length .…”
Section: Figure 14mentioning
confidence: 99%
“…(2020) considered both the solutocapillary effect of soluble surfactant and the thermocapillary effect, and reached the same conclusion. Kalogirou & Blyth (2019, 2020, 2021) investigated a two-layer shear flow with soluble surfactant dissolving in the lower layer. They reported that solubility and sorption kinetics could influence interfacial dynamics and the effect of soluble surfactant on the instability could be either stabilizing or destabilizing.…”
Section: Introductionmentioning
confidence: 99%